Precise Clock Synchronization Algorithm for Distributed Control Systems - Yi Liu; Haiying Yang (Institute of Advanced Engineering and Science, 2013)
The distributed control systems are applied widely in communication, navigation and power fields. With growing in both systems complexity and speed of data exchange, the real time performance of systems is required. Existing clock synchronization techniques include those for wide-area network (WAN) applications with large propagation delays, e.g., the Network Time Protocol (NTP), and those for control systems over local-area networks (LANs), e.g., the IEEE 1588 Precise Time Protocol (PTP). However, NTP-like protocols have only millisecond-scale precision, which is too coarse for many LAN applications such as instrument monitoring systems, high-quality digital audio systems and sensor networks. The 1588 PTP like protocols, which are still under development, require support of a highly precise hardware clock. The key point of the existing Ethernet test and measurement is that the method needs to achieve precision clock synchronization between different terminals. In this paper, an improved method is proposed with consideration of the time drift and propagation delay, expressing master-slave synchronization as a linear relationship and inducting the line of least squares fitting algorithm that traded as linear matrix form. The precision time protocol (PTP) is also analyzed in this paper. The experiment results show that the synchronization accuracy reaches sub-microsecond grade, which is the same as the PTP. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2832